2022
DOI: 10.22302/iccri.jur.pelitaperkebunan.v38i1.496
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Illegal Small-Scale Mining (Galamsey) on Cocoa Farming and Farmer Livelihood: A Case Study in the Amansie West District of Ghana

Abstract: Cocoa and gold are significant contributors to the gross dormestic product of Ghana which makes both commodities key parts of the Ghanaian economy. Unfortunately, in Ghana, most cocoa-growing communities are the hub of illegal small-scale mining commonly known as galamsey. It is alleged that cocoa farmerssell their farmlands for galamsey; however, given that cocoa farming is the primary source of income for many households in rural Ghana. This research aimed at investigating the motivations for galamsey and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The same explanation could also be given to the lncocoa variable. The negative effect of such activities has been emphasized by (Boakye 2020;Laari 2018;Osman et al 2022;Wedam et al 2014) Gold and Diamond production (lngold and India) variables showed a positive and significant effect. The significance is shown in Model 1 for both and Model 3 for only gold.…”
Section: Resultsmentioning
confidence: 97%
“…The same explanation could also be given to the lncocoa variable. The negative effect of such activities has been emphasized by (Boakye 2020;Laari 2018;Osman et al 2022;Wedam et al 2014) Gold and Diamond production (lngold and India) variables showed a positive and significant effect. The significance is shown in Model 1 for both and Model 3 for only gold.…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have reported on the weight gain effect of Moringa oleifera. Interestingly, none of these studies have indicated the leaf type, which was used, however, the finding from these studies have revealed that both young and old leaves of Moringa oleifera possesses similar effect of body weight [18]- [21].…”
Section: Body Weightmentioning
confidence: 99%
“…The average yearly temperature is 25.5°C, while the wet season's relative humidity ranges from 75 to 80%. Most of the vegetation is a degraded semideciduous forest (Osman et al, 2022). Mining activity represents the main possible source of heavy metals contamination in the area because the town has a long history of mining and has had continuous mining operations since the 1890s.…”
Section: Area Of Studymentioning
confidence: 99%